How do self-fulfilling prophecies affect financial ratings? An experimental study - Sanela Celjo-Hörhager; Alexandra Niessen (University of Cologne, Centre for Financial Research (CFR), 2006)
In this experimental study we examine the impact of self-fulfilling prophecies on financial ratings. According to theoretical models like Kuhner (2001), rating agencies are more likely to reveal their private information if their rating can not become self-fulfilling from an ex-post point of view. In our experiment we use two settings in which ratings differ with respect to the degree of their self-fulfilling impact. In connection with a strong self-fulfilling impact of ratings we indeed observe that agencies are more likely to assign ratings which are not in line with their private information. Our results support theoretical findings of Kuhner (2001). However, the pathological equilibrium predicted by the theoretical model does not emerge in our experiment.
Keywords: D82; F34; G23; 330; Self-fulfilling Prophecies; Financial Ratings; Asymmetric Information